Understanding Participants' Perceptions of Access to and Satisfaction With Chronic Disease Prevention Programs. (August 2019) - Perry, Rebecca; Gard Read, Jennifer; Chandler, Caroline; Kish-Doto, Julia; Hoerger, Thomas
Despite the promise of incentive-based chronic disease prevention programs, comprehensive evidence on their accessibility among low-income populations remains limited. We adapted Aday and Andersen's framework to examine accessibility and consumer satisfaction within the Medicaid Incentives for the Prevention of Chronic Disease (MIPCD) cross-site demonstration. MIPCD provided 10 states with 5-year grants to implement incentivized chronic disease prevention and management programs for low-income and/or disabled—Medicaid enrolled—Americans. We conducted 36 focus group discussions between July 2014 and December 2015 with Medicaid enrollees participating in the MIPCD programs. We assessed participants' satisfaction by program type (i.e., diabetes prevention, diabetes management, hypertension reduction, smoking cessation, and weight management) related to three components: program enrollment and participation, staff courtesy, and program convenience. Based on Aday and Andersen's framework, we conducted thematic analysis to determine similarities and differences across MIPCD programs by type. Participant feedback confirmed the importance of several features of the Aday and Andersen framework, particularly programs with easy enrollment and participation procedures, courteous and helpful staff, and those that are convenient and flexible for participants. Participants valued programming around the clock via telephone and flexible, in-person hours of operation as well as proximity of the program to reliable transportation. We observed that most participants, despite enrollment and participation barriers, perceived programs as accessible and were willing to engage and continue to participate. This finding may reflect behavior change theory's perspective on personal readiness to change. Individuals in the preparation stage of change can effectively change health habits despite barriers they may encounter. In some cases, personal readiness to change was more impactful than consumer satisfaction at encouraging ongoing participation and perceived access to the programs. Thus, program developers may want to consider individual participant readiness to change and its impact on consumer satisfaction when designing, implementing, and evaluating behavior change initiatives.